ANALYSIS OF STUDENT CONTRIBUTIONS TO THE SUSTAINABILITY OF UNIVERSITAS SEBELAS MARET’S GREEN CAMPUS PROGRAM - Albertus Erico Jerry Krisna Nugroho; Siska Dwi Utami; Agung Hidayat (Universitas Sebelas Maret (UNS), 2025)
Higher Education Institutions are trying to contribute to take part in addressing environmental sustainability issues to answer challenges and reduce the impact of environmental damage. Universitas Sebelas Maret (UNS) Surakarta implemented the Green Campus Program to create an environmentally friendly and sustainable higher education environment. This study aims to analyze the role of students in efforts to support the sustainability of the Green Campus Program at Universitas Sebelas Maret. The research method used is descriptive with a mix method approach that involves 120 UNS students as randomly selected respondents spread across various levels and faculties. Data was collected through a questionnaire based on UI Green Metric categories. The results of this study indicate that 82% of students obtained “Strongly Support” in playing a role in supporting the sustainability of the Green Campus Program. Students show their role in contributing proactively and taking full initiative based on UI Green Metric categories related to environmental issues at the University. Students have an important role as agents of change in environmental sustainability on campus. These findings are expected to provide insights for universities in maximizing student involvement for the improvement and success of the Green Campus Program.